Cardiometabolic Health in Relation to Diet and Physical Activity: Experimental and Clinical Evidence - Mahmoud, Abeer M.; Phillips, Shane (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The purpose of this Special Issue, "The Role of Nutrition in Cardiometabolic Health: Experimental, Clinical, and Community-Based Evidence", is to publish a focused, coherent, impactful, and well-cited volume on how nutrition influences diverse cardiometabolic risk factors. Cardiometabolic diseases such as coronary heart disease, stroke, type 2 diabetes mellitus, and obesity are the leading causes of death worldwide. In recent years, dietary habits have shifted all over the globe. At the same time, a constantly growing body of evidence demonstrates the role of caloric intake and dietary composition as determinants of cardiometabolic health. A suboptimal diet predisposes to a myriad of cardiometabolic risk factors such as impaired glucose metabolism, insulin resistance, dyslipidemia, and high blood pressure. The goal of this Special Issue is to provide rigorous evidence from novel experimental and observational studies that support the association between dietary factors and cardiometabolic risk and evaluate the diverse diet-related risk pathways.